Implementasi Pendidikan Seksualitas Anak melalui Pembelajaran Fikih (Studi Multisitus di MI As-Sunniyyah 45 Kencong dan MIMA 34 Hasyim Asy’ari Ambulu Jember) - Dukan Jauhari Faruq (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The implementation of sexuality education in schools provides an important role for child development. With sexuality education through fiqh learning, the teacher can provide habituation and instill the value of responsibility in children by introducing the duties and functions of the limbs based on the gender of the child. This study aims to determine (1) how is the implementation of child sexuality education through the learning of the chapter of the Thaharah chapter of fiqh? This research used a qualitative descriptive approach with a multi-site study, because it was conducted in two educational institutions, namely MIMA 34 Hasyim Asy'ari Ambulu Jember and MI 45 As-Sunniyyah Kencong Jember. Data collection techniques through interviews (with the principal, maple jurisprudence teacher, homeroom teacher, and students), observation, and documentation study developed through research instruments. The results of the research are as follows (1) The implementation of child sexuality education through the learning of the thaharah chapter of fiqh is through: (a) the material on menstruation, circumcision, and the limitations of baligh; (b) the methods used are lectures, question and answer and storytelling; (c) the selected media is a blackboard. (2) Implementation of child sexuality education through fiqh learning in the prayer chapter is through: (a) material on genitals and the differences between men and women in prayer; (b) the methods used are lectures, questions and answers, and demonstrations; (c) the media chosen is a three-dimensional visual tool in the form of artificial objects such as barbie dolls and real objects in the form of students themselves.